Water Quality Parameters for the Culture of Rainbow Trout, Oncorhynchus mykiss (Walbaum) in the Raceways of Kathmandu, Nepal - Bhagat, Rakesh Prasad; Barat, Sudip (Our Nature, 2015)
Eighteen water quality parameters (5 physical, 9 chemical, 2 climatic and 2 geographical) were investigated for the water quality assessment so as to know whether water in the raceways from spring-fed torrential stream at a high altitude was feasible and suitable for the culture of rainbow trout, Oncorhynchus mykiss (Walbaum) or not. Results indicated colourless, odourless, and crystal-clear water throughout the year with air temperature ranging from 11.4-26.9 (20.3±1.1oC), water temperature 8.4-21.5 (16±1.1oC), water velocity 1.5-3.5 (2.5±0.11m sec-1), water discharge 37-92 (56±2.87L sec-1), turbidity 3-19 (11± 1.04NTU), pH 6.5-8.2 (7.44±0.11), electrical conductivity 35-204 (112.13±11.2µS cm-1), dissolved oxygen 5.9-10.5 (8.2±0.3mg L-1), free carbon dioxide 1.4-5.1 (3.6±0.2mg L-1), total alkalinity 17-97 (55.1±5.32mg L-1), total hardness 11-90 (47±5.06mg L-1), phosphate-P 0.01-0.50 (0.14±0.02mg L-1), ammonium-N 0.09-0.91 (0.28 ±0.04mg L-1), nitrate-N 0.01-0.83 (0.17±0.04mg L-1), relative humidity 62.4-88.7 (75.01±1.59%), rainfall 0.0-503.4 (132.44±32.83mm), altitude 1550msl, and water resource stream-fed torrential stream. Correlation analyses of the parameters showed strongest correlation at the significance level of 0.01. All parameters were positively correlated except pH, electrical conductivity, dissolved oxygen, total alkalinity, and total hardness which were negatively correlated with rest. Parameters of the first year were slightly higher than second due to fluctuation in temperature, velocity and discharge, relative humidity, and rainfall influenced by climatic factors, geography, seasons, and environment of the origin and occurrence of the water resource, thus affecting rest of the parameters. Water velocity and water discharge could be maintained as per requirement of the culture. These parameters were within permissible limits being feasible and suitable for rainbow trout culture. Our Nature (2015), 13(1): 50-57